The Value of Laparoscopic Simultaneous Colorectal and Hepatic Resection for Synchronous Colorectal Cancer Liver Metastasis: A Propensity Score Matching Study - Zhou, Jiamin; Feng, Longhai; Li, Xinxiang; Wang, Miao; Zhao, Yiming; Zhang, Ning; Wang, Longrong; Zhang, Ti; Mao, Anrong; Xu, Ye; Wang, Lu (Frontiers in Oncology, 2022)
Purpose: To investigate the value of total laparoscopic simultaneous colorectal and hepatic resection in the patients with synchronous colorectal cancer liver metastases (sCRLM). Methods: sCRLM patients underwent simultaneous resection from December 2014 to December 2018 in Shanghai Cancer Center, Fudan University were recruited and analyzed retrospectively. The patients were divided into laparoscopic, open and hybrid surgery group. The intraoperative information, postoperative short-term outcome and long-term survival were compared among the three groups. Propensity score matching (PSM) was performed to balance baseline. Results: A total of 281 patients were recruited. After PSM, 34 patients were selected from both laparoscopic and open surgery group. Forty-seven patients were also selected from both laparoscopic and hydrid surgery group. The clinicopathologic baselines between laparoscopic surgery group and the other two groups were well matched. All the operation related indicators between laparoscopic surgery and hydrid surgery were similar. However, compared with open surgery, laparoscopic surgery showed significantly longer operation time (229.09 ± 10.94 vs 192.24 ± 9.49, P = 0.013) and less intraoperative blood loss (100.00 (50.00-300.00) vs 200.00 (150.00-400.00), P = 0.021). For postoperative morbidity, there was no significant difference between laparoscopic surgery group and hydrid or open surgery groups (23.40% vs 31.91% and 17.65% vs 26.47%, P = 0.356 and P = 0.380). Long-term survival analysis showed that there was no significant difference in all 1-, 3-, 5-year overall survival, liver recurrence free survival (RFS) and whole RFS between laparoscopic surgery and hydrid surgery (P = 0.334, P = 0.286 and P = 0.558) or open surgery (P = 0.230, P = 0.348 and P = 0.450). Conclusions: Laparoscopic simultaneous resection for sCRLM showed slight advantages in surgical safety and short-term outcome, and does not compromise long-term survival.